An In-Depth Review of Gold Nanoparticle Applications in Healthcare and Environmental Sustainability (International Journal of Food and Nutritional Sciences, 2022)
Nanotechnology has achieved significant progress through the creation of functional, engineered nanoparticles within the nanoscale range of 1-100 nm. These minuscule particles are transforming various fields, such as medicine and electronics, by providing innovative solutions to complex problems. In nanomedicine, the use of nanomaterials has shown considerable advantages in treatment procedures, offering new curative effects and perspectives for tackling various diseases. The swift advancement of nanoscale delivery systems has facilitated their application in diagnosis and targeted drug delivery with controlled and monitored precision. Gold nanoparticles (AuNPs) are particularly well-suited for biomedical applications due to their ease of synthesis, stability, customizability, low toxicity, and ease of detection. These characteristics make AuNPs a promising tool for early disease detection, diagnosis, and treatment, especially in medical imaging, drug delivery, and cancer therapy. This article examines recent research on the use of gold nanoparticles as drug delivery systems in medicine and targeted drug delivery